2015
DOI: 10.1260/1747-9541.10.4.757
|View full text |Cite
|
Sign up to set email alerts
|

Drive Performance for Able-Bodied and Disabled Golfers

Abstract: Golf is a popular leisure and competitive activity for individuals with disabilities. The current golf handicap system does not take into account the possible challenges of playing golf with any form of physical disability. The aim of this study was to examine golf driving performance measures, comparing golfers with various types of physical disabilities to able-bodied golfers. Through drive shot ball launch analysis, this study compared amputees (single leg, below and above knee), deaf, visually impaired, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The current handicap system, for example, does not take into account the possible challenges of playing golf with any form of physical disability. As such, Kenny et al (2015) argue that disabled golfers are currently penalised / disadvantaged by the handicap classification rules as it does not take into consideration either the possible unique challenges of playing golf with any form of disability, or the potential effects of a disability on performance. It is argued that opportunities to promote golf as a lifelong physical activity among people with disabilities may be missed in clubs where personnel are unsure of the barriers and facilitators to participation outlined here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current handicap system, for example, does not take into account the possible challenges of playing golf with any form of physical disability. As such, Kenny et al (2015) argue that disabled golfers are currently penalised / disadvantaged by the handicap classification rules as it does not take into consideration either the possible unique challenges of playing golf with any form of disability, or the potential effects of a disability on performance. It is argued that opportunities to promote golf as a lifelong physical activity among people with disabilities may be missed in clubs where personnel are unsure of the barriers and facilitators to participation outlined here.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies around exercise and stroke tend to focus on the physical benefits and there are few studies on emotional well-being in stroke patients (Schachten, & Petra, 2015). Despite the potential of golf, participation by disability groups remains low, and out of those who do play there is little transition into regular participation (Kenny, 2015;Piggott, Leslie, & Poller, 2011;Sandt, Flynn, & Turner, 2014).…”
Section: Golf Participation For Stroke Survivorsmentioning
confidence: 99%
“…Golf is not yet as popular among disabled people as it is among their nondisabled counterparts 7 and has high dropout rates and a small transition rate into regular participation. [13][14][15] Identifying factors that are barriers to participation is important.…”
Section: What Is Newmentioning
confidence: 99%
“…Many of the personal, environmental, and social barriers are similar to those reported regarding general participation in disability sports. 15,[23][24][25] Ives et al, 24 for instance, also reported various internal barriers, such as anxiety about sporting ability and external barriers, including transport and other logistical barriers. Organizational barriers worth considering include the cost of playing, being able to afford the equipment, club membership, and costs associated with entering and traveling to tournaments (especially as the golfers often paid costs for their guide).…”
Section: The Facilitators and Barriers To Playing VI Golfmentioning
confidence: 99%
See 1 more Smart Citation